Sabinin AIgebras: The Basis of a Nonassociative Lie Theory (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
Certain famous concepts and results such as Universal enveloping algebras, Poincaré-Birkhoff-Witt Theorem and the Lie correspondence have been, up to some extend, synonymous of Lie algebras.